2005
DOI: 10.1158/1078-0432.ccr-04-2119
|View full text |Cite
|
Sign up to set email alerts
|

FAS/FAS Ligand Ratio: A Marker of Oxaliplatin-Based Intrinsic and Acquired Resistance in Advanced Colorectal Cancer

Abstract: Purpose: Oxaliplatin-5-fluorouracil combinations have increased responses in first-line therapy up to 40% in advanced colorectal cancer. Unfortunately, those patients who will respond are unknown and initially sensitive patients become rapidly resistant to current therapies. FAS (CD95) and FAS ligand (FASL; CD95L) have been implicated in chemosensitivity through leading to apoptosis in response to DNA-damaging drugs.Whereas the proapoptotic role of FAS and FASL is well characterized, the function of their solu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 22 publications
2
17
1
Order By: Relevance
“…Moreover, in another study, specific cleavage of Fas by MMP-7 resulted in decreased sensitivity of HT-29 colon carcinoma cells to Fas-mediated apoptosis. 43 In the same study, the authors found a markedly increased susceptibility of these cells to Fas-mediated apoptosis when their MMP-7 expression was suppressed by transient transfection of the antisense oligonucleotide for this proteinase. There is then a strong suggestion that increased levels of MMP-7 are associated with the development of refractoriness to chemotherapy agents.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Moreover, in another study, specific cleavage of Fas by MMP-7 resulted in decreased sensitivity of HT-29 colon carcinoma cells to Fas-mediated apoptosis. 43 In the same study, the authors found a markedly increased susceptibility of these cells to Fas-mediated apoptosis when their MMP-7 expression was suppressed by transient transfection of the antisense oligonucleotide for this proteinase. There is then a strong suggestion that increased levels of MMP-7 are associated with the development of refractoriness to chemotherapy agents.…”
Section: Discussionmentioning
confidence: 88%
“…Our group and others, have demonstrated that MMP-7 blocks lymphocyte cytotoxicity, by cleaving of the NH 2 -terminal ''preligand assembly domain'' of FAS membrane (FASm) 41 and the extracellular surface of FASL membrane (FASLm) 17 leading to a decreased sFAS/sFASL ratio, 42 and therefore escaping from the immune system and favoring resistance to chemotherapy. Recently, Wang et al 43 have demonstrated that MMP-7 increases resistance to Fas-mediated apoptosis and, the authors conclude that high MMP-7 tissue expression is a poor prognostic factor of patients with CRC. Vargo-Gogola et al 44 have determined that FASL cleavage from the cell surface by MMP-7 provides apoptosis resistance and subsequently leads to tumor formation in murine mammary glands.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28,40,41 Increment in the ratio of soluble FAS to FAS ligand/CD95 by enzyme-linked immunosorbent assay in blood after treatment with oxaliplatin and 5-FU combination chemotherapy has been reported as a marker of chemosensitivity in advanced colorectal cancer patients, and decreased ratio as a predictor of chemoresistance. 42 It seems likely that the finding is a generic effect for platinum agents, rather than specific to oxaliplatin. Favorable germline genotypes from polymorphisms in XPD-751, ERCC1-188, GSTP1-105, and TS-3 0 -untranslated region have also been associated with improved survival in this setting.…”
Section: Markers For Oxaliplatinmentioning
confidence: 99%
“…The role of FAS/FASL and TRAIL systems in CRC patients treated with chemotherapeutic agents was discussed in some reported studies (Nadal et al 2005;van Geelen et al 2006;Granci et al 2008). To the best of our knowledge, the changes in the levels of these markers in MCRC patients treated with bevacizumab-based regimens have not been described yet.…”
Section: Introductionmentioning
confidence: 99%